Cloning and structural elucidation of a brassinosteroids biosynthetic gene (Atdwarf4) and genetic transformation of Indian mustard (Brassica juncea L.) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Phytohormones play critical roles in plant growth and development. Brassinosteroids (BRs) are essential group of phytohormones required for optimum growth of plants and their deficiency causes distinctive dwarf phenotypes in plants. Homeostasis of BRs in plants is maintained by DWARF4 enzyme that mediates multiple 22α-hydroxylation steps in brassinosteroid biosynthesis. Arabidopsis plants over-expressing DWARF4 show increase in inflorescence, number of branches and siliques; thereby increased number of seeds/plant. This suggests that engineering DWARF4 biosynthesis in Brassica plant can be strategized to enhance yield in mustard. In the present study (i) we cloned dwarf4 gene from Arabidopsis using gene specific PCR strategy, (ii) elucidated the three-dimensional structure of DWARF4 protein at molecular level where it revealed presence of four beta sheets and 20 alpha-helices, and (iii) transformed mustard cultivar Pusa Jaikisan with an objective to develop transgenic mustard with enhanced number of siliques. We obtained several putative transgenics with an average transformation efficiency of 3.3%. Molecular characterization with nptII specific primers confirmed presence of transgene in six putative transgenic plants.